Multicultural Education In Social Perspective - Afi Parnawi; Abdullah Idris (International Journal of Technology and Education Research, 2023)
This article discusses the concept of multicultural society from a sociological perspective, using the Indonesian state as a historical aggregator of diverse ethnic groups, nations, religions, and beliefs as a case study. There are times when variety in Indonesia leads to conflict, but there are other instances where the nation's diversity serves as a source of strength to shield each other from being crushed by the progress of time. Equipped to understand multiculturalism is not limited to intellectuals or community leaders; rather, knowing multiculturalism is required at all levels, layers, and tiers of society. As a result of the media's exaggeration of SARA (ethnicity, religion, race, and inter-group) concerns, the Indonesian populace is currently extremely vulnerable to catastrophic social changes. To prevent a recurrence of "bloody conflict" tragedies, it will always be necessary to discuss diversity, keeping in mind that generations are always changing. This research aims to reintroduce the concept of multiculturalism to the younger generation, as well as to all levels of society in general, and not simply academic debate. This paper's methodology involves library research and the presentation of incidents that have occurred in Indonesia. Based on the results of the study presented in the discussion chapter, it can be inferred that the concept of multiculturalism in Indonesia does not originate from the outside, i.e., that old indigenous knowledge helped strengthen the condition of multicultural society. But, because community members do not have equal access to education, the potential for horizontal conflict has always persisted. In the context of the repercussions of a pluralistic society in Indonesia, the seeds of conflict inside a diversified structure might become dormant dangers to the social order. Because there are no longer any constraints on the public's ability to absorb information, local concerns will rapidly become national ones.